THE RELATIONSHIP BETWEEN THE PORTER AND THE COORDINATOR AT THE KEPUTRAN MARKET AS A MANIFESTATION OF TECHNICAL PROTECTION IN EMPLOYMENT LAW - M Lutfi Rizal Farid (Universitas Muhammadiyah Mataram, 2025)
This study aims to provide a prescription regarding the legal relationship that occurs between porters and coordinators at Keputran Market. The research method used is legal research using primary legal materials, secondary legal materials and non-legal materials to answer the legal issues studied. In addition, this legal research also uses a statutory regulatory approach and a conceptual approach to strengthen the legal materials used. The results and discussions obtained are that the relationship between porters and coordinators at Keputran Market is not included in the category of an employment relationship, so that health and safety as in the concept of technical protection known in labor law cannot be applied. In fact, the work carried out is full of impacts received for health and safety.